Variations of clinical SPECT/CT operations - Wieder, H.; Freudenberg, L. S.; Czernin, J.; Navar, B. N.; Israel, O.; Beyer, T. (Nuklearmedizin - NuclearMedicine, 2012)
Aim: This survey gathers information about clinical SPECT/CT operations worldwide to help guide standardization of clinical SPECT/ CT imaging. Methods: An international, webbased survey of SPECT/CT users was initiated in 12/2010 through an e-mail distribution. Users were asked 71 questions related to (A) demographics, (B) SPECT/CT operations/utilization and (C) variations in imaging protocols. Results: Collected responses originated from 117 imaging centers in the Americas (66%), Europe (20%), Asia-Pacific (11%) and the Middle-East (3%), with the majority of responding sites representing public health care institutions (69%). Most sites operate 1–2 SPECT/CT-systems (74%), typically installed in Nuclear Medicine departments (84%) with extensive prior SPECT-only experience (82%). Only 14% of SPECT/CTs are installed in Radiology departments. Clinical SPECT/CT imaging is performed either as routine (51%) or ad-hoc “add-on” procedure (49%) with a high inter-site and inter-examination variability. The main application of the integrated CT is to provide anatomical localization of the tracer uptake rather than to produce contrast enhanced or other high-quality CT images. Consequently, in only 22% of the sites a CT contrast injector is installed. Only 6% of centers use SPECT/CT devices for stand-alone CT procedures. Conclusion: An international survey among clinical SPECT/CT users revealed that SPECT/CT is a not a routine component of nuclear medicine procedures. The majority of the centers responding do not fully utilize the diagnostic potential of the CT components. Significant variations in standard imaging protocols were observed. These findings illustrate the need for training and standardization and underscore the need for revisiting the role of SPECT/CT in diagnostic imaging.
Keywords: SPECT/CT; clinical operations; imaging protocols